Examining the Intersection of Corporate Social Responsibility and Social Entrepreneurship: Community Empowerment in Mining Sector - Hamdi Mayulu; Ni Nyoman Suryani; Prihutomo Suharto; Cori Qamara; Riki Andika; I Putu Gede Didik Widiarta (Agriwar Journal, 2025)
The mining industry, particularly in regions such as Samarinda East Kalimantan, has induced substantial socio-economic and environmental challenges, including land degradation, ecosystem disruption, and an over-reliance on an unstable economic sector. These challenges further exacerbate the vulnerabilities of local communities, particularly those dependent on traditional agricultural practices, which are increasingly threatened by environmental deterioration. In response to these issues, Corporate Social Responsibility (CSR) has emerged as a pivotal strategy for mitigating the adverse effects of mining operations. CSR initiatives, particularly those fostering social entrepreneurship, aim to promote sustainable livelihoods and community development. This study examines the impact of CSR-driven cattle farming programs in Bali as a means of community empowerment in mining-affected regions. Employing a mixed-methods approach, the research integrates qualitative and quantitative data gathered through surveys, semi-structured interviews, and field observations from 50 households in villages affected by mining activities. The findings reveal that CSR initiatives supporting Bali cattle farming have substantially enhanced household incomes, increased livestock ownership, and generated new employment opportunities. Additionally, these initiatives have contributed to environmental restoration, particularly in improving soil quality and reducing erosion in previously degraded areas. The results highlight the potential of CSR programs to promote long-term economic resilience and environmental sustainability in post-mining regions, thereby contributing to community empowerment and ecological restoration.